2016
DOI: 10.1007/s11695-016-2232-y
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Endoscopy Prior to Bariatric Surgery: a Systematic Review and Meta-Analysis of the Literature

Abstract: A selective approach to preoperative EGD may be considered, based on the patients' symptoms, risk factors, and type of procedure planned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(26 citation statements)
references
References 18 publications
0
24
0
2
Order By: Relevance
“…Esophagogastroscopy can be considered as routine diagnostic test prior to bariatric surgery Conditional recommendation Changes of medical management included primarily H. pylori eradication and initiation of proton-pump inhibitors or histamine blockers for gastritis or reflux [41]. The second meta-analysis demonstrated similar findings [42].…”
Section: Preoperative Endoscopy Versus No Endoscopy In Patients Undermentioning
confidence: 94%
“…Esophagogastroscopy can be considered as routine diagnostic test prior to bariatric surgery Conditional recommendation Changes of medical management included primarily H. pylori eradication and initiation of proton-pump inhibitors or histamine blockers for gastritis or reflux [41]. The second meta-analysis demonstrated similar findings [42].…”
Section: Preoperative Endoscopy Versus No Endoscopy In Patients Undermentioning
confidence: 94%
“…Yet, in one notable exception in a primarily Chinese population with obesity, routine preoperative upper‐GI endoscopy demonstrated significant abnormalities . Systematic reviews, meta‐analyses, and other retrospective studies have demonstrated benefit of preoperative endoscopy in patients with GI symptoms, where results altered surgical planning in roughly 7 to 12% of patients . A retrospective study by Yormaz et al found that in patients undergoing bariatric surgery, the Gastrointestinal Symptom Rating Scale and upper‐GI symptoms were independent predictive markers of abnormalities found with preoperative esophagogastroduodenal endoscopy.…”
Section: Executive Summarymentioning
confidence: 99%
“…On EGDS, only minor abnormalities were detected that were considered clinically insignificant: non-HP gastritis, mild or moderate degree esophagitis, or gastric mucosa erosions. It is clear that management of these disorders does not require a delay in elective surgery, nor is it a contraindication for operation [ 11 ]. In 4 cases, esophagitis (LA grade A/B) was found to be associated with hiatal hernia, and 2 of these reported reflux complaints.…”
Section: Discussionmentioning
confidence: 99%